Seasonal temperatures from δ18O in recent Spanish tufa stromatolites: Equilibrium redux!. Issue 5 (17th February 2018) - Arenas, Concha; Osácar, MARÍA Cinta; Auqué, Luis Francisco; Andrews, Julian E.; Pardo, Gonzalo; Marca, Alina; Martín‐Bello, Leticia; Pérez‐Rivarés, Francisco Javier
Abstract: This study focuses on recent debate over the value of stable isotope‐based environmental proxies recorded in riverine tufa stromatolites. A twelve‐year record (1999 to 2012) of river‐bed tufa stromatolites in the River Piedra (north‐east Spain) was recovered in this study, along with a partly overlapping fifteen‐year record (1994 to 2009) of accumulations in a drainage pipe: both deposits formed in water with near identical physico/chemical parameters. Measured water temperature data and near‐constant δ 18 Owater composition allowed selection of an 'equilibrium' palaeotemperature equation that best replicated actual temperatures. This study, as in some previous studies, found that just two published formulas for water temperature calculation from equilibrium calcite δ 18 O compositions were appropriate for the River Piedra, where tufa deposition rates are high, with means between 5·6 mm and 10·8 mm in six months. The δ 18 Ocalcite in both the river and the pipe deposits essentially records the full actual seasonal water temperature range. Only the coldest times (water temperature <10°C), when calcite precipitation mass decreased to minimum, are likely to be unrepresented, an effect most noticeable in the pipe where depositional masses are smaller and below sample resolution. While kinetic effects on δ 18 Ocalcite ‐based calculated water temperature cannot be ruled out, the good fit between measured water temperature and δ 18 Ocalcite ‐calculated water temperature indicates that temperature is the principal control. Textural and deposition rate variability between the river and pipe settings are caused by differences in flow velocity and illumination. In the river, calcification of growing cyanobacterial mat occurred throughout the year, producing composite dense and porous laminae, whereas in the pipe, discontinuous cyanobacterial growth in winter promoted more abiogenic calcification. High‐resolution δ 18 Ocalcite data from synchronous pipe and river laminae show that reversals in water temperature occur within laminae, not at lamina boundaries, a pattern consistent with progressive increase in calcite precipitation rate as cyanobacterial growth re‐established in spring.